A New Theory of Demand-Restricted Growth - Thomas Gries (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Mainstream growth theory is dominated by variations of the neoclassical approach. Growth is explained fully by elements of the supply side. In this paper we examine the general mechanism of technology growth and capital accumulation. However, instead of following a fully supply-side driven neoclassical approach we suggest a hybrid approach that allows for growth restrictions induced by demand-side elements. We obtain a demand-restricted growth by suggesting an unconventional equilibrium concept in a stochastic environment. We define macroeconomic equilibrium as stationary no-expectation-error equilibrium. This equilibrium concept relates to the Nash idea of individual stationary behavior as long as expectations prove to be realized. No rigidities are introduced. Even if potential growth is generated by technical change and capital accumulation, the level of the path and the growth rate are restricted by effective earnings. Both can be stable below the neoclassical potential growth. The growth rate in the demand restricted regime is semi-endogenous and determined by entrepreneurial conditions and activities. However, the growth process mutates to the neoclassical process if effective earnings are sufficient and the earnings ratio turns to one. As a result, the demand side cannot generate growth, but the demand side can permanently restrict growth which could have been generated by the supply side. Our hybrid model could help to bridge a gap between Keynesian and neoclassical ideas of economic growth.
Keywords: E12; E13; O40; E60; 330; Demand restricted growth; no-expectation-error equilibrium; neoclassical growth theory